Sosialisasi Pencegahan Diri Dari Tb Paru Di Puskesmas Pb Selayang II Medan - Endang Maryanti; Neni Ekowati Januariana; Indah Anggraini; Putri Aisyah Aprillia (Institut Teknologi dan Bisnis Semarang, 2023)
Pulmonary Tuberculosis is an infectious disease that is transmitted by Mycobacterium tuberculosis. Until now, Pulmonary Tuberculosis is still one of the main public health problems in the world even though efforts to control Tuberculosis have been carried out in various countries. This disease, if left untreated, will cause death. The purpose of health promotion is to socialize self-prevention from TB. Lung. This community service uses a quantitative approach by using a questionnaire sheet as an instrument to find out the experiences of patients who have pulmonary TB and other communities to prevent it early. The post-test value with an average of 90.78% of participants answered correctly higher than the pre-test value of 81.32%. The knowledge of the community at the PB Selayang II Medan Health Center increased between 80-90% after being given counseling on self-prevention from TB Lung. The counseling used in a simple way with the lecture and demonstration method made the community understand about self-prevention from TB Lung. The conclusion is that the posttest results show that the community’s knowledge is better than the posttest that has been done.